Susceptibilidad a los problemas de salud y correlatos de personalidad - Reig Ferrer, A.; Rodríguez Marín, J.; Sancho Jane, P.; Ribera Domene, D.; García Rodríguez, J. A. (Análisis y Modificación de Conducta, 1986)
Sin resumen